A survey on Predictive Analysis in Employment Trends - Radhakrishnan, Nita; Awasthi, Mehul; Mahalakshmi, P (International Journal of Engineering and Technology, 2018)
This paper addresses the theories of using predictive analysis and Data Mining in arriving at suitable patterns and predicting paths and trends in the current Employment Scenario more specifically to the Engineering sector. India produces 1.5 million engineers every year, and yet there is a significant gap between their skills and the jobs and corresponding salaries they are offered. Recognizing the factors that inï¬‚uence this gap can help us bridge it. The survey shows that the ideal route to doing so, is by employing various Predictive analysis and Data Mining techniques on appropriate data sets, which help in addressing these issues. As per the survey, appropriate visualization techniques have also been used to extract the meaning from the prediction and analysis.Â Â